VIOLENCE AGAINST WOMEN: BETWEEN NORMATIVENESS RELIGIOUS AND JURIDICAL INTERPRETATION OF MUBADALAH PERSPECTIVE - Rahmi, Atikah (Proceeding International Seminar of Islamic Studies, 2024)
The juridical legitimacy of men's position as leaders who have authority in the interpretation of the verses of the Qur'an has implications for violence against women in the household. Biased interpretations of religious texts and legal regulations that do not clearly regulate the protection of women victims of violence are typical problems in acts of domestic violence. This research focuses on documentation studies based on text studies. This method is used to explore data, facts and theories that make a belief true. Normative legal studies are carried out by focusing on the study of text interpretation, statutory regulations and Islamic law to find comparisons. This article aims to review the interpretation of verses from the Koran which have been very masculine by using the concept of mubindah. Through this article, the concept of mubjadi will change the horizon of thinking towards unequal men and women to be balanced, so that violence and injustice against women can be prevented.